The Influence of Acquisition Delay for Calibration-Free Laser-Induced Breakdown Spectroscopy. Issue 3 (March 2016) - Fu, Hongbo; Dong, Fengzhong; Ni, Zhibo; Wang, Jingge
Time-resolved spectra of neutral and ionized atomic emissions from slag sample are measured by laser-induced breakdown spectroscopy (LIBS). Various factors affecting the calibration-free CF-LIBS method are carefully analyzed, and subsequently these factors are either avoided or corrected. Plasma temperature and electron density are calculated by Saha–Boltzmann plot and Stark broadening of Ca, respectively. At the same time, self-absorption and local thermodynamic equilibrium have been carefully studied. An automatic spectral lines elimination algorithm is applied to calculate plasma temperature and element concentration. The calculated element concentrations show marked changes with acquisition time increasing. Due to the influence of continuous spectrum at early times and self-absorption at late times, the large absolute errors sum is obtained in these two periods. The smallest absolute errors sum corresponds to the gate delay time 1.5 μs < td < 2 μs for our experimental setup.